2004
DOI: 10.1038/sj.cdd.4401443
|View full text |Cite
|
Sign up to set email alerts
|

Omomyc expression in skin prevents Myc-induced papillomatosis

Abstract: Obligate sensitization to apoptosis provides a safeguard mechanism against the oncogenic potential of Myc. Omomyc is a mutant bHLHZip domain that sequesters Myc in complexes that are unable to bind to the E box recognition element and activate transcription but remain competent for transcriptional repression. Omomyc has the peculiar properties of reverting Myc-induced transformation of tissue culture cells and enhancing Myc proapoptotic function. Thus, Omomyc has the potential to act as a potent suppressor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 19 publications
1
59
0
Order By: Relevance
“…Primary antibodies were as follows: rabbit polyclonal anti-Omomyc [prepared in-house, Evan labora-tory (Soucek et al 2004)] and mouse monoclonal anti-p21 (clones SX118 and SXM30, BD Pharmingen). Primary antibodies were applied for 2 h in blocking buffer (2.5% BSA, 5% goat serum, 0.3% Triton X-100 in PBS), sections were washed, and speciesappropriate secondary Alexa fluor 488 dye-conjugated antibodies (Amersham) or Vectastain ABC kit and DAB reagents (Vector Laboratories) were applied.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Primary antibodies were as follows: rabbit polyclonal anti-Omomyc [prepared in-house, Evan labora-tory (Soucek et al 2004)] and mouse monoclonal anti-p21 (clones SX118 and SXM30, BD Pharmingen). Primary antibodies were applied for 2 h in blocking buffer (2.5% BSA, 5% goat serum, 0.3% Triton X-100 in PBS), sections were washed, and speciesappropriate secondary Alexa fluor 488 dye-conjugated antibodies (Amersham) or Vectastain ABC kit and DAB reagents (Vector Laboratories) were applied.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Omomyc retains the ability to bind its physiological partner, Max, but also heterodimerizes with wild-type c-Myc, N-Myc, and L-Myc proteins. Since Myc:Omomyc heterodimers can no longer bind to the canonical Myc E-box CACGTG DNA recognition element, Omomyc overexpression inhibits Myc-dependent target gene transactivation (Soucek et al 2002(Soucek et al , 2004Savino et al 2011). Omomyc is therefore a competitive inhibitor of Myc transcriptional activation, and we used it to model pharmacological inhibition of Myc by generating mice (TREOmomyc) in which Omomyc expression is driven from a tetracycline-responsive promoter element.…”
mentioning
confidence: 99%
“…To address these questions directly, we combined the RIP1-Tag2 pancreatic b-cell mouse tumor model with our TRE-Omomyc;CMVrtTA mouse, in which the dominantnegative Myc inhibitor Omomyc (Soucek et al 1998(Soucek et al , 2002(Soucek et al , 2004 may be reversibly induced systemically in vivo (Soucek et al 2008). Omomyc competitively blocks Myc/Max heterodimerization and binding to the E-box, thus inhibiting the capacity of Myc proteins to transactivate target genes (Soucek et al 1998(Soucek et al , 2002.…”
mentioning
confidence: 99%
“…However, the development of the Myc-interfering molecule termed Omomyc, which binds c-and N-Myc, Max, and Miz-1 but does not bind Mad or certain HLH proteins, has demonstrated that it might cause edge-specific perturbations in the Myc interactome that destroy specific protein interactions of the Myc node while leaving others intact. [117][118][119][120][121][122][123] This results in a "rewriting" of the Myc transcriptome in a manner that produces opposing effects on the 2 arms of Myc activity, namely transactivation and transrepression of gene transcription. Specifically, Omomyc prevents Myc binding to promoter E-boxes and the transactivation of target genes while allowing Myc to retain Miz-1-dependent binding to promoters and transrepression function.…”
Section: Gerometabolites and Oncometabolites Share A Communication LImentioning
confidence: 99%